2020
DOI: 10.1186/s12967-020-02320-0
|View full text |Cite
|
Sign up to set email alerts
|

The emerging role of the long non-coding RNA HOTAIR in breast cancer development and treatment

Abstract: Despite considering vast majority of the transcribed molecules as merely noise RNA in the last decades, recent advances in the field of molecular biology revealed the mysterious role of long non-coding RNAs (lncRNAs), as a massive part of functional non-protein-coding RNAs. As a crucial lncRNA, HOX antisense intergenic RNA (HOTAIR) has been shown to participate in different processes of normal cell development. Aberrant overexpression of this lncRNA contributes to breast cancer progression, through different m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(55 citation statements)
references
References 119 publications
1
54
0
Order By: Relevance
“…HOTAIR is considered to be a significant diagnostic marker for many neoplasms, including breast cancer, cervical cancer, or colorectal cancer. 87 , 88 , 89 Moreover, HOTAIR is considered to be one of the first tumor-related lncRNAs to have been discovered. It is associated with metastasis development and poor patient prognoses.…”
Section: Main Textmentioning
confidence: 99%
“…HOTAIR is considered to be a significant diagnostic marker for many neoplasms, including breast cancer, cervical cancer, or colorectal cancer. 87 , 88 , 89 Moreover, HOTAIR is considered to be one of the first tumor-related lncRNAs to have been discovered. It is associated with metastasis development and poor patient prognoses.…”
Section: Main Textmentioning
confidence: 99%
“…HOTAIR was proposed to function as a scaffold to facilitate the recruitment of PRC2 and LSD1/CoREST/REST epigenetic complexes to increase H3K27me3 and H3K4me2, respectively, on targeted genomic loci [216][217][218]. Since p21 expression is regulated by PRC2 in lung cancer cells, it is possible that the upregulation of HOTAIR can promote the recruitment of PRC2 to downregulate p21 expression in lung adenocarcinoma cells [219,220]. However, the artificial chromatin tethering of HOTAIR in breast cancer cells caused transcription repression independently of PRC2 [221].…”
Section: Lncrnas In Solid Tumorsmentioning
confidence: 99%
“…Moreover, estradiol can bind with the estrogen response element in the promoter region of this lncRNA. Notably, HOTAIR activity has a crucial role in the induction of ER signaling in malignant cells [37]. Another study in prostate cancer cells revealed opposite functions of metastasis associated lung adenocarcinoma transcript 1 (MALAT1) and HOTAIR in estrogen-associated transcriptional modulation.…”
Section: Lncrnas and Er Functions In Cancersmentioning
confidence: 99%